Beyond the First Generation of Wind Modeling for Resource Assessment and Siting: From Meteorology to Uncertainty Quantification - Mark Kelly (Energies)
Increasingly large turbines have led to a transition from surface-based ‘bottom–up’ wind flow modeling and meteorological understanding, to more complex modeling of wind resources, energy yields, and site assessment. More expensive turbines, larger windfarms, and maturing commercialization have meant that uncertainty quantification (UQ) of such modeling has become crucial for the wind industry. In this paper, we outline the meteorological roots of wind modeling and why it was initially possible, advancing to the more complex models needed for large wind turbines today, and the tradeoffs and implications of using such models. Statistical implications of how data are averaged and/or split in various resource assessment methodologies are also examined, and requirements for validation of classic and complex models are considered. Uncertainty quantification is outlined, and its current practice on the ‘wind’ side of the industry is discussed, including the emerging standard for such. Demonstrative examples are given for uncertainty propagation and multi-project performance versus uncertainty, with a final reminder about the distinction between UQ and risk.